2021
DOI: 10.3906/sag-2103-235
|View full text |Cite
|
Sign up to set email alerts
|

Hidden threat in familial Mediterranean fever: subclinical inflammation, oxidative stress and their relationship with vitamin D status

Abstract: Background/aim: Vitamin D levels have been investigated in children with familial Mediterranean fever (FMF), but the relationship between vitamin D status and inflammation/oxidative stress indicators could not be clearly demonstrated. This study aimed to investigate the relationship between subclinical inflammation/oxidative stress and vitamin D status in children with FMF during an attack-free period. Materials and methods:In the cross-sectional study, ninety children with FMF in the attack-free period and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Several studies have elucidated the correlation between serum vitamin D levels and disease activity in pediatric FMF patients [6][7][8]. These studies often employ the measurement of 25-hydroxyvitamin D [25(OH)D], the primary circulating form of vitamin D, to assess vitamin D status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have elucidated the correlation between serum vitamin D levels and disease activity in pediatric FMF patients [6][7][8]. These studies often employ the measurement of 25-hydroxyvitamin D [25(OH)D], the primary circulating form of vitamin D, to assess vitamin D status.…”
Section: Introductionmentioning
confidence: 99%
“…These studies often employ the measurement of 25-hydroxyvitamin D [25(OH)D], the primary circulating form of vitamin D, to assess vitamin D status. It has been observed that pediatric patients with active FMF tend to have significantly lower levels of 25(OH)D compared to those in remission and healthy controls [8,9]. This deficiency may be linked to the pro-inflammatory state of FMF, as vitamin D is known to exert antiinflammatory effects through the inhibition of proinflammatory cytokines such as IL-1, IL-6, and TNF-α [8,10].…”
Section: Introductionmentioning
confidence: 99%